The Paris Agreement: Destined to Succeed or Doomed to Fail? - Young, Oran R. (2016)
Is the 2015 Paris Agreement on climate change destined to succeed or doomed to fail? If all the pledges embedded in the intended nationally determined contributions (INDCs) are implemented fully, temperatures at the Earth’s surface are predicted to rise by 3–4 °C, far above the agreement’s goal of limiting increases to 1.5 °C. This means that the fate of the agreement will be determined by the success of efforts to strengthen or ratchet up the commitments contained in the national pledges over time. The first substantive section of this essay provides a general account of mechanisms for ratcheting up commitments and conditions determining the use of these mechanisms in international environmental agreements. The second section applies this analysis to the specific case of the Paris Agreement. The conclusion is mixed. There are plenty of reasons to doubt whether the Paris Agreement will succeed in moving from strength to strength in a fashion resembling experience with the Montreal Protocol on ozone depleting substances. Nevertheless, there is more room for hope in this regard than those who see the climate problem as unusually malign, wicked, or even diabolical are willing to acknowledge.